2020
DOI: 10.1021/acsami.9b19096
|View full text |Cite
|
Sign up to set email alerts
|

Reconciliation of Differences in Apparent Diffusion Coefficients Measured for Self-Exchange Electron Transfer between Molecules Anchored to Mesoporous Titanium Dioxide Thin Films

Abstract: Redox-active sites present at large concentrations as part of a solid support or dissolved as molecules in fluid solutions undergo reversible self-exchange electron-transfer reactions. These processes can be monitored using a variety of techniques. Chronoamperometry and cyclic voltammetry are common techniques used to interrogate this behavior for molecules bound to mesoporous thin films of wide-bandgap semiconductors and insulators. In order to use these techniques to obtain accurate values for apparent diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…This observation initially appears counter‐intuitive since the Ru complex is immobilized and the Ru 2+ /Ru 3+ redox reaction does not involve proton transfer (Figure 3B), and therefore we might instead expect a linear relationship between the current density and scan rate. However, this “diffusion‐limited” redox behavior originates from the self‐exchange electron transfer among the Ru complexes immobilized on TiO 2 surface [18] . Unlike free molecules in solutions, where redox reactions occur via the mass transport and subsequent interfacial electron transfer, the complexes immobilized on the surface of metal oxides experience inhibited molecular motion and enhanced molecule‐molecule interactions [18,19] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation initially appears counter‐intuitive since the Ru complex is immobilized and the Ru 2+ /Ru 3+ redox reaction does not involve proton transfer (Figure 3B), and therefore we might instead expect a linear relationship between the current density and scan rate. However, this “diffusion‐limited” redox behavior originates from the self‐exchange electron transfer among the Ru complexes immobilized on TiO 2 surface [18] . Unlike free molecules in solutions, where redox reactions occur via the mass transport and subsequent interfacial electron transfer, the complexes immobilized on the surface of metal oxides experience inhibited molecular motion and enhanced molecule‐molecule interactions [18,19] .…”
Section: Resultsmentioning
confidence: 99%
“…However, this “diffusion‐limited” redox behavior originates from the self‐exchange electron transfer among the Ru complexes immobilized on TiO 2 surface [18] . Unlike free molecules in solutions, where redox reactions occur via the mass transport and subsequent interfacial electron transfer, the complexes immobilized on the surface of metal oxides experience inhibited molecular motion and enhanced molecule‐molecule interactions [18,19] . Due to the limited electrical conductivity of metal‐oxide substrates, the redox reactions of the surface‐bound complexes primarily occur through self‐exchange electron transfer instead of direct interfacial electron transfer from the electrode, which results in the linear dependence of peak current densities on the square root of scan rates [18] …”
Section: Resultsmentioning
confidence: 99%
“…Much scientific creativity can be exercised in the design of redox polymers for (i) efficient DET and mediated electron transfer (i.e., redox polymer as an electron shuttle) at the biocatalyst-electrode interface, (ii) biocatalyst immobilization and/or preservation of biocatalyst functionality, (iii) maintaining biocatalyst-electrode stability, and (iv) extending additional, case-specific functionalities to electrodes (e.g., multi-functional polymers in which solvation degree is governed by external triggers such as pH or temperature). 1,12 Electrocatalytically significant polymers can be broadly categorized into: (i) conducting polymers (CPs), (ii) redox polymers (RPs), [13][14][15] and (iii) conducting redox polymers (CRPs), based on chemical structure and respective charge transfer mechanisms. CPs shuttle charge carriers through their π-conjugated backbones.…”
Section: List Of Symbols αmentioning
confidence: 99%
“…The basal plane contains carbon with sp 2 hybridization; it is flat with low defect density, while the edge plane contains sp 3 sites, functional groups, dangling bonds, and defects due to the abrupt lattice termination. The electrochemical activity of the basal plane is very low and depends on the history and the number of defects on the surface. ,, Also, it has been shown that the rate of electron transfer strongly depends on the presence of specific active sites on the surface such as hydrogen-bonding sites and O- and N-containing functional groups. ,, So, diverse physical, chemical, thermal, electrochemical, and other treatment methods have been developed to improve one or more physical and/or chemical properties of carbonous materials. , Carbonous materials due to the high-affinity adsorption are gradually contaminated, and their treatment is critical for their use in electrochemical measurements. ,,, …”
Section: Introductionmentioning
confidence: 99%